Mineral content and phytochemical properties of selected Caulerpa species from Malaysia - Ismail, Mohd Fakhrulddin; Ramaiya, Shiamala Devi; Zakaria, Muta Harah; Mohd Ikhsan, Natrah Fatin; Awang, Mohd Azrie (Faculty of Science, University of Malaya, 2020)
Seaweeds are abundant and are an important renewable resource for the coastal community since they are rich sources of minerals and natural bioactive compounds. Among them, the Caulerpa species under green seaweeds is widely consumed by locals in Southeast Asia. Edible seaweeds are often associated with various health benefits. However, in Malaysia, limited studies have been done on the mineral and antioxidant levels of seaweeds, especially for the Caulerpa species. Thus, the present study aimed to evaluate the variations of minerals and antioxidants of selected Caulerpa species in Malaysia. The samples were collected in two study sites, which were Blue Lagoon, Port Dickson and Merambong Shoal, Johor. Two species, C. racemosa and C. manorensis were recorded from Merambong Shoal, Johor, while five species were recorded namely C. sertularioides, C. racemosa var lamourouxii, C. lentillifera, C. racemosa var cylindracea and C. racemosa at Blue Lagoon, Port Dickson. Among all the Caulerpa species from both study sites, C. manorensis possessed the highest phosphorus content (139.54 mg/100g) while C. racemosa from both Merambong and Blue Lagoon Port Dickson’s calcium (Ca) content was significantly highest at 2318.33 – 2406.66 mg/100g. All the Caulerpa species possessed high sodium (Na) content ranging 9338.30 – 21748.30 mg/100g. For micronutrients, the highest zinc content was recorded in C. manorensis (3.40 mg/100g) while the copper content was significantly highest in C. racemosa from Port Dickson (1.05 mg/100g). The methanol extract of C. sertularioides possessed phytochemical attributes of high antioxidant activity (DPPH EC50 = 24.16 mg/mL) with a high FRAP value being recorded in C. lentillifera (27.09 mg TE/100g). The TPC and TFC were highest in C. lentillifera with 57.95 mg GAE/100g and 1506.41 mg QE/100g respectively. The present study revealed that Caulerpa species contained constituents with significant mineral compositions and phytochemical attributes suitable for pharmaceutical and nutraceutical uses.